2022
DOI: 10.1039/d2an00157h
|View full text |Cite
|
Sign up to set email alerts
|

Detecting bacterial infections in wounds: a review of biosensors and wearable sensors in comparison with conventional laboratory methods

Abstract: Bacterial infection is a common impediment towards wound healing. Detecting bacterial infections is important to promote wound healing and curb chronic non-healing wounds. In this review, we firstly discuss bacterial...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 112 publications
2
13
0
Order By: Relevance
“…Besides that, correct pathogen identification based on culture often requires vast expertise, which might lead to inaccurate diagnosis [ 27 ]. To minimize such inaccuracy in biochemical methods, analytical profile index (API) tests [ 28 ] and automated systems such as VITEK (bioMerieux, Inc., Marcy-l’Étoile, France) have been developed [ 29 ].…”
Section: Current Methods For the Clinical Diagnosis Of Bacterial Infe...mentioning
confidence: 99%
“…Besides that, correct pathogen identification based on culture often requires vast expertise, which might lead to inaccurate diagnosis [ 27 ]. To minimize such inaccuracy in biochemical methods, analytical profile index (API) tests [ 28 ] and automated systems such as VITEK (bioMerieux, Inc., Marcy-l’Étoile, France) have been developed [ 29 ].…”
Section: Current Methods For the Clinical Diagnosis Of Bacterial Infe...mentioning
confidence: 99%
“…If this keeps happening, the wound can become chronic and stop healing. [43][44][45][46] Therefore, it is vital to remove the contaminating microbes during the inflammation phase. In recent decades, numerous antibacterial agents have been developed and the existence of antibacterial materials could be classified into the following types: antibiotics, antibacterial nanoparticles and others.…”
Section: Factors Affecting Wound Healingmentioning
confidence: 99%
“…The presence of Gram-positive bacteria is notable in the early stages of infection, whereas Gram-negative bacteria appear in the stably established wounds. 43,45,46 According to the findings of recent clinical trials, using contemporary wound dressings may be the most convenient, affordable, and successful way to treat unhealed wounds. As a result, wound dressing development has a lot of potential.…”
Section: Antibacterial Propertymentioning
confidence: 99%
“…It has been reported that adhesion proteins present on the surface of bacteria are rich in hydrophobic domains, which make them easy to adhere to hydrophobic interfaces, thereby causing infection. , According to the hydrophobic characteristics of the bacterial surface, hydrophobic antibacterial agents are expected to target bacteria through hydrophobic interaction to achieve high-efficiency antibacterial effects. , For instance, Yang and his team prepared a thermosensitive gel layer (TRGL)-containing, MOF-derived nanocarbon-based ZnO-CNP-TRGL composite that offers hydrophobic interaction to target bacteria and exhibits NIR-responsive photothermal activity and Zn 2+ releasing activity . The TRGL possessed high hydrophilicity at room temperature, which makes the ZnO-CNP-TRGL well dispersed and thus having low bacterial interaction ability.…”
Section: Bacterial-targeted Precise Antibacterial Strategiesmentioning
confidence: 99%
“…Common wound infections can occur in burn wounds, combat-related wounds, surgical wounds, or chronic wounds like diabetic ulcers . With the aggravation of infection, pus may appear at the wound site and may eventually lead to nonhealing of the wound, which not only affects the patient’s normal life but also creates substantial financial burden . Thus, bacterial infection of wounds should be detected and treated as soon as possible.…”
Section: Emerging Applications Of Samnsmentioning
confidence: 99%